2006
DOI: 10.1111/j.1600-6143.2005.01218.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA Susceptibility to BKV Infection

Abstract: We read with interest the article by Bohl et al. titled 'Donor origin of BK virus in renal transplantation and role of HLA C7 in susceptibility to sustained BK viremia' (Am J Transplant 2005; 5: 2213-2221. The authors' observations on the HLA C7 locus prompted us to examine the HLA typing data on our own patients with BKV nephropathy, who presented 11 ± 6.8 months after transplantation. On a retrospective review, data on HLA Cw loci were available in 31 recipients (23 Caucasians, 8 African Americans), of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…Because BKPyV-specific T cell responses are %50to 100-fold lower than those to cytomegalovirus, these assays have not readily entered clinical practice. Moreover, the risk factors for BKPyV replication and nephropathy vary in different KT studies and include steroid pulses for acute rejection, maintenance immunosuppression such as tacrolimus-mycophenolate versus cyclosporine-mycophenolate, older age of recipients, male sex and a higher number of HLA mismatches (37)(38)(39)(40)(41)(42)(43)(44)(45). According to the recent Organ Procurement and Transplantation Network and Scientific Registry of Transplant Recipients report, these risk factors are present in a substantial number of KT patients (46).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Because BKPyV-specific T cell responses are %50to 100-fold lower than those to cytomegalovirus, these assays have not readily entered clinical practice. Moreover, the risk factors for BKPyV replication and nephropathy vary in different KT studies and include steroid pulses for acute rejection, maintenance immunosuppression such as tacrolimus-mycophenolate versus cyclosporine-mycophenolate, older age of recipients, male sex and a higher number of HLA mismatches (37)(38)(39)(40)(41)(42)(43)(44)(45). According to the recent Organ Procurement and Transplantation Network and Scientific Registry of Transplant Recipients report, these risk factors are present in a substantial number of KT patients (46).…”
mentioning
confidence: 99%
“…According to the recent Organ Procurement and Transplantation Network and Scientific Registry of Transplant Recipients report, these risk factors are present in a substantial number of KT patients (46). Moreover, organs from BKPyV IgG-positive donors for recipients with low or undetectable antibodies may face an increased risk (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found the study by Awadallah et al (1), to be provocative in that it showed that the presence of the MHC class I allele, HLA C7, was not sufficient to prevent BKV nephropathy in renal transplant recipients. The authors state that this contrasts with our own study showing that persistent BK viremia correlated with the absence of HLA C7 (2).…”
mentioning
confidence: 87%
“…Matching of HLA-A2, B44, and DR15 may be protective against BK viremia, 84 and the absence of C7 in either the donor or the recipient may be a risk factor for BK infection, 17 a result that was not confirmed in another cohort. 85 …”
Section: Immunology Of Pvanmentioning
confidence: 99%